STUDENT CENTER FAKULTAS TEKNIK UNIVERSITAS LAMBUNG MANGKURAT - Ripai, Achmat; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The Student Center of the Faculty of Engineering Lambung Mangkurat University aims to improve facilities for students and student organizations. The problems faced are how to design a Student Center that can accommodate collaboration between student activities and student organizations. Programming methods are used to solve architectural problems and find solutions. A review of references and case studies from several Student Centers globally provides insight into the importance of paying attention to context, dividing functional zones, and providing facilities that support various student activities in the Student Center. The design concept initiated is connectivity in the form of physical and visual connectivity with an emphasis on spatial layout, activity zones and similar materials. As a result, the space in the Student Center is dynamic according to student needs.